Crystal structure of anhydrous potassium O-n-propyldithiocarbonate. Theoretical calculations of O-alkyl dithiocarbonates - Buntine, Mark; Cox, M.; Lim, Y.; Yap, T.; Tiekink, E. (R Oldenbourg Verlag, 2003)
The xanthate anion in the structure of K[S(2)COnPr] displays the expected features, i.e. planar S2CO chromophore and variation in C-S and C-O distances. The K cation exists in a distorted cubic geometry defined by an O2S6 donor set. Cubes are face-shared so as to form a layer structure with cohesion between layers afforded by hydrophobic interactions. A series of theoretical gas-phase structures have been calculated for isolated S2COR anions. These show that there is a remarkable consistency in geometric parameters across the series. This observation indicates that the nature of the R substituent does not influence greatly the electronic structure of the central S2CO chromophore.